2007
DOI: 10.1097/qad.0b013e3282f12f41
|View full text |Cite
|
Sign up to set email alerts
|

Same race and older partner selection may explain higher HIV prevalence among black men who have sex with men

Abstract: In a community-based survey in San Francisco, black men who have sex with men (MSM) had higher rates of same-race/ethnicity sexual partnerships and partners 10 or more years older compared with other MSM. Differences in sexual networks may explain why black MSM have higher HIV prevalence than other MSM despite lower levels of risk behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
130
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 7 publications
14
130
2
Order By: Relevance
“…10,12,16,17 Recent studies have underscored the importance of focusing on and understanding sexual networks by race and prior research has observed a significant tendency among Black MSM to have more partners of the same race. 13,22,24 Consistent with previous studies, 13,22,24 Black MSM in the current sample had more partners who were Black men (49%) and fewer Hispanic/Latino (40%) or White (13%) male partners. However, in contrast with prior research, relative to participants who had sex last with a White male, participants who had sex last with a Hispanic/Latino male were more likely to have engaged in UAS and those who had sex with a Black male were less likely to report engaging in UAS.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…10,12,16,17 Recent studies have underscored the importance of focusing on and understanding sexual networks by race and prior research has observed a significant tendency among Black MSM to have more partners of the same race. 13,22,24 Consistent with previous studies, 13,22,24 Black MSM in the current sample had more partners who were Black men (49%) and fewer Hispanic/Latino (40%) or White (13%) male partners. However, in contrast with prior research, relative to participants who had sex last with a White male, participants who had sex last with a Hispanic/Latino male were more likely to have engaged in UAS and those who had sex with a Black male were less likely to report engaging in UAS.…”
Section: Discussionsupporting
confidence: 87%
“…20,21 Studies have more recently begun to underscore the importance of focusing on and understanding racial dynamics in sexual networks. 13,[22][23][24] For example, Laumann and Youm demonstrated that the incidence and prevalence of HIV and STDs remained higher within Black populations because Black men and women were more likely than White and Latino men and women to have sex exclusively with partners of the same race who were more likely to be HIV-and/or STD-infected. 22 In more recent research focused on MSM, Bingham and colleagues found that racial differences in male partner types partially accounted for elevated rates of HIV infection by examining the role of partner characteristics among 400 MSM ages 23 to 29 in the Los Angeles Young Men's Survey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Hernandez-Romieu et al found that HIV prevalence among Black MSM sexual networks was 36% compared to only 4% among White MSM sexual networks. 15 Previous studies have used these findings to propose that higher HIV incidence and prevalence among Black MSM may be explained by same race 1,3,[16][17][18][19] or older partners. 1,7,16,20,21 However, other analyses have contested the relationship between HIV incidence and partner race 22 or partner age.…”
Section: Introductionmentioning
confidence: 99%
“…15 Previous studies have used these findings to propose that higher HIV incidence and prevalence among Black MSM may be explained by same race 1,3,[16][17][18][19] or older partners. 1,7,16,20,21 However, other analyses have contested the relationship between HIV incidence and partner race 22 or partner age. 22,23 An analysis of the National HIV Behavioral Surveillance System found that sexual networks were not influential in explaining the HIV disparity between White and Black MSM.…”
Section: Introductionmentioning
confidence: 99%